2008
DOI: 10.2478/v10001-008-0036-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Thai Version of the 22-Item and 45-Item Karasek Job Content Questionnaire

Abstract: Objectives: To evaluate the validity and reliability of the Thai version of the job content questionnaire (TJCQ) both 22-item and 45-item versions. Materials and Methods: The study encompassed 10,450 employees in Songkhla province, Thailand. A 45-item job content questionnaire (JCQ) was translated and back translated complying with the JCQ usage policy. TJCQ covers seven scales as follows: psychological demand, decision latitude, supervisor support, coworker support, physical demand, job security and hazard at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 39 publications
6
30
0
4
Order By: Relevance
“…The studies that tested JCQ reliability and validity (mostly, decision latitude, psychological job demands, supervisor support, and co-worker support scales) have generally found acceptable psychometric characteristics and substantial comparability of the JCQ scales across populations (Choi et al, 2009;Fransson et al, 2012;Jabali et al, 2013), despite some exceptions, as is the case of the psychological job demands scale, that shows low internal consistency in some studies (Kawakami et al, 1995;Phakthongsuk, & Apakupakul, 2008). The studies also found different results in the decision latitude scale that can challenge the theoretical framework: some identify two factors in that scale -skill discretion and decision authority (Chien et al, 2011;Karasek et al, 1998;Smith, Tisak, Hahn, & Schmieder, 1997) -, and others only one factor (Niedhammer et al, 2006;Pelfrene et al, 2001;Phakthongsuk, & Apakupakul, 2008;Zotnierczyk-Zreda, & Bedyriska, 2014).…”
Section: Assessing Stress At Work: the Portuguese Version Of The Job mentioning
confidence: 99%
“…The studies that tested JCQ reliability and validity (mostly, decision latitude, psychological job demands, supervisor support, and co-worker support scales) have generally found acceptable psychometric characteristics and substantial comparability of the JCQ scales across populations (Choi et al, 2009;Fransson et al, 2012;Jabali et al, 2013), despite some exceptions, as is the case of the psychological job demands scale, that shows low internal consistency in some studies (Kawakami et al, 1995;Phakthongsuk, & Apakupakul, 2008). The studies also found different results in the decision latitude scale that can challenge the theoretical framework: some identify two factors in that scale -skill discretion and decision authority (Chien et al, 2011;Karasek et al, 1998;Smith, Tisak, Hahn, & Schmieder, 1997) -, and others only one factor (Niedhammer et al, 2006;Pelfrene et al, 2001;Phakthongsuk, & Apakupakul, 2008;Zotnierczyk-Zreda, & Bedyriska, 2014).…”
Section: Assessing Stress At Work: the Portuguese Version Of The Job mentioning
confidence: 99%
“…Part 2 was on job stress. The Thai version of the Job Content Questionnaire (JCQ) 24) was used. This consisted of 22 questions measuring 3 dimensions: psychological job demand, decision latitude, and workplace social support.…”
Section: Instrumentationmentioning
confidence: 99%
“…Each item had a response set of a four-point Likert scale ranging from 1, strongly disagree, to 4, strongly agree 27) . Participants were also required to answer the question "Have you, during the past month, experienced muscular tension during work?"…”
Section: Biopsychosocial Risk Factorsmentioning
confidence: 99%